BREAST - Pimenta, Renata Moura; Garcia, Cecília Alcântara Braga (Seven Editora, 2026)
The breasts are superficial and prominent anatomical structures on the anterior chest wall, primarily in women due to their reproductive function and the lactation process during pregnancy, but they are also present in men, although they are more rudimentary and non-functional, formed only by a few small ducts or epithelial cords. However, in general, the fat present in male breasts is no different from the subcutaneous tissue found in other parts of the body, and there is usually no development of the glandular system. (MOORE; DALLEY; AGUR, 2014). The origin of the word breast comes from the Latin "mamma," which in turn means breast. They are a group of glands derived from the epidermis, developed from the ectoderm and mesoderm. They are located in the subcutaneous tissue, over the pectoralis major and minor muscles, between the second and sixth ribs, extending medially to the sternum and laterally to the anterior border of the latissimus dorsi muscle. (DÂNGELO; FATTINI, 2003) DOI: https://doi.org/10.56238/sevened2026.002-012